Monetary policy, bank bailouts and the sovereign-bank risk nexus in the euro area - Malte Rieth; Marcel Fratzscher (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The paper analyses the empirical relationship between bank risk and sovereign credit risk in the euro area. Using structural VAR with daily financial markets data for 2003-13, the analysis confirms two-way causality between shocks to sovereign risk and bank risk, with the former being overall more important in explaining bank risk, than vice versa. The paper focuses specifically on the impact of non-standard monetary policy measures by the European Central Bank and on the effects of bank bailout policies by national governments. Testing specific hypotheses formulated in the literature, we find that bank bailout policies have reduced solvency risk in the banking sector mostly at the expense of raising the credit risk of sovereigns. By contrast, monetary policy was in most, but not all cases effective in lowering credit risk among both sovereigns and banks. Finally, we find spillover effects in particular from sovereigns in the euro area periphery to the core countries.
Keywords: E52; G10; E60; 330